New Insight into Inter-kingdom Communication: Horizontal Transfer of Mobile Small RNAs - Zhou, Geyu; Zhou, Yu; Chen, Xi (Frontiers in Microbiology, 2017)
Small RNAs (sRNAs), including small interfering RNAs (siRNAs) and microRNAs (miRNAs), are conventionally regarded as critical molecular regulators of various intracellular processes. However, recent accumulating evidence indicates that sRNAs can be transferred within cells and tissues and even across species. In plants, nematodes and microbes, these mobile sRNAs can mediate inter-kingdom communication, environmental sensing, gene expression regulation, host-parasite defence and many other biological functions. Strikingly, a recent study by our group suggested that ingested plant miRNAs are transferred to blood, accumulate in tissues and regulate transcripts in consuming animals. While our and other independent groups’ subsequent studies further explored the emerging field of sRNA-mediated crosstalk between species, some groups reported negative results and questioned its general applicability. Thus, further studies carefully evaluating the horizontal transfer of exogenous sRNAs and its potential biological functions are urgently required. Here, we review the current state of knowledge in the field of the horizontal transfer of mobile sRNAs, suggest its future directions and key points for examination and discuss its potential mechanisms and application prospects in nutrition, agriculture and medicine.